Investigating information and communication technology (ICT) usage, knowledge sharing and innovative behavior among engineers in electrical and electronic MNCs in Malaysia - Hazril Izwar Ibrahim,; Wan Maisara Wan Mohamad,; Khairul Anuar Mohammad Shah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Innovative behavior is vital for organizations as competition based on innovation can serve as a basis for sustainable development, especially for multinational companies in the Electrical and Electronic sector in Malaysia. Grounded by the social cognitive theory, this study utilized a research framework examining ICT usage as a predictor of innovative behavior with knowledge sharing (knowledge giving and knowledge receiving) as mediating variables. A total of 309 engineers from multinational companies in the electrical and electronic manufacturing firms in Malaysia participated in this study. By using partial least squares structural equation modeling (PLS-SEM) for analysis, the study revealed that ICT usage has a significant relationship with knowledge receiving. It also found that knowledge receiving played a mediating role in the relationship between ICT usage and innovative behavior. The findings of this study are useful to both academics and practitioners who wish to understand the predictors of innovative behavior so that the innovative behavior can be inculcated among organizational members, and thus, increasing the success of the companies.